The Effect of Self-Efficiency on Employee Performance in Cooperative at Bali - Zuhriyah, Nur Azizah; Juhary, Ali (2023)
The purpose of this study is to explain and explore the relationship between self-efficacy and business performance in cooperatives in Bali. The development of cooperatives in the province of Bali is very rapid so that the number of active cooperatives is 4193 spread over 9 districts / cities. The research sample was 54 cooperatives from nine cities and districts. Each cooperative represented as many as 3 employees to be respondents. So the total sample size is 162 people. Data collection using questionnaires has been distributed to 162 respondents. The data is processed using a quantitative approach assisted by SPSS 25 software. The results of the research show that self-efficacy has a significant effect on employee performance in Bali.